COVID-19 Vaccine Hesitancy: The Perils of Peddling Science by Social Media and the Lay Press - Shabeer Ali Thorakkattil; Suhaj Abdulsalim; Mohammed Salim Karattuthodi; Mazhuvanchery Kesavan Unnikrishnan; Muhammed Rashid; Girish Thunga (Vaccines, 2022)
Introduction: Vaccines are the best tools to end the pandemic, and their public acceptance is crucial in achieving herd immunity. Despite global efforts to increase access to vaccination, the World Health Organization explicitly lists vaccination hesitancy (VH) as a significant threat. Despite robust safety reports from regulatory authorities and public health advisories, a substantial proportion of the community remains obsessed with the hazards of vaccination. This calls for identifying and eliminating possible causative elements, among which this study investigates the inappropriate dissemination of medical literature concerning COVID-19 and adverse events following immunization (AEFI), its influence on promoting VH, and proposals for overcoming this problem in the future. Methods: We searched PubMed, Embase, and Scopus databases, using the keywords “adverse events following immunization (AEFI)”, “COVID-19”, “vaccines” and “hesitancy” and related medical and subjective headings (MeSH) up to 31 March 2022, and extracted studies relevant to the COVID-19 AEFI and associated VH. Finally, 47 articles were chosen to generate a narrative synthesis. Results: The databases depicted a steep rise in publications on COVID-19 AEFI and COVID-19 VH from January 2021 onwards. The articles depicted multiple events of mild AEFIs without fatal events in recipients. While documenting AEFIs is praiseworthy, publishing such reports without prior expert surveillance can exaggerate public apprehension and inappropriately fuel VH. VH is a deep-rooted phenomenon, but it is difficult to zero in on the exact reason for it. Spreading rumors/misinformation on COVID-19 vaccines might be an important provocation for VH, which includes indiscriminately reporting AEFI on a massive scale. While a number of reported AEFIs fall within the acceptable limits in the course of extensive COVID-19 vaccinations, it is important to critically evaluate and moderate the reporting and dissemination of AEFI in order to allay panic. Conclusions: Vaccination programs are necessary to end any pandemic, and VH may be attributed to multiple reasons. VH may be assuaged by initiating educational programs on the importance of vaccination, raising public awareness and monitoring the inappropriate dissemination of misleading information. Government-initiated strategies can potentially restrict random AEFI reports from lay epidemiologists and healthcare practitioners.